2009
DOI: 10.3402/jom.v1i0.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of subgingival and buccalCandida dubliniensisisolates in immunocompetent subjects assessed by RAPD-PCR

Abstract: BackgroundIt is recognized that Candida dubliniensis commonly colonizes oral and subgingival sites in immunocompetent subjects with periodontal disease.ObjectiveSince there are few data available on genetic characterization of C. dubliniensis in periodontal pockets and other oral sites, the aim of this study was to characterize subgingival and mucosal C. dubliniensis isolates recovered from immunocompetent subjects and to assay the genetic similarity of such isolates from both niches in the same patient by ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Jewtuchowicz et al identified Candida dubliniensis in a sample of 240 patients who were alcohol and drug addicts. The incidence of Candida dubliniensis was 4.6% in the subgingival biofilm ( 18 , 19 ). Our results concur with the results of the aforementioned authors on the incidence of Candida dubliniensis in HIV-negative patients addicted to psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…Jewtuchowicz et al identified Candida dubliniensis in a sample of 240 patients who were alcohol and drug addicts. The incidence of Candida dubliniensis was 4.6% in the subgingival biofilm ( 18 , 19 ). Our results concur with the results of the aforementioned authors on the incidence of Candida dubliniensis in HIV-negative patients addicted to psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…Primers 5, 6, and 7 amplified a random sample amounting to 0.37% of the whole genome which is a limitation of this study. However, several studies had demonstrated that PCR-based DNA fingerprinting using a small number of primers is suitable to examine genetic diversity in E. coli [60], Candida dubliniensis [61], and mackerel [62]. Another limitation is that DNA fingerprinting was performed on the entire population and not on isolated colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Cuesta et al [27] reported a value of 13% of the genus Candida of which 76.2% were Candida albicans in a population of 82 with 56 chronic periodontitis, which is confirmed by several studies and which also reported that Candida albicans was the most frequent species in periodontal pockets by 21.7% to 24.4% [12,28].…”
Section: Discussionmentioning
confidence: 68%
“…According to previous studies, the distribution of Candida albicans isolates from the subgingival biofilm according to periodontal health status varied between 9,5% and 40% in subjects with chronic periodontitis, whereas in healthy subjects, the presence of Candida albicans was estimated between 3.8% and 36% [11,26,[28][29][30][31][32] and 20% in patients with aggressive periodontitis [6]. In our study, Candida albicans was recovered in the periodontal pockets of 25 (37%) subjects with periodontitis versus 17% without periodontitis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation